HIV prevention metrics: lessons to be learned from contraception. Issue 8 (5th August 2022) - Pyra, Maria; Heffron, Renee; Haberer, Jessica E.; Kiarie, James
Abstract: Introduction: As the range of effective HIV prevention options, including multiple biomedical tools, increases, there are many challenges to measuring HIV prevention efforts. In part, there is the challenge of varying prevention needs, between individuals as well as within individuals over time. The field of contraception faces many similar challenges, such as the range of prevention methods and changing contraceptive needs, and has developed many metrics for assessing contraceptive use at the program level, using frameworks that move beyond the HIV prevention cascade. We explore these similarities and differences between these two prevention fields and then discuss how each of these contraceptive metrics could be adapted to assessing HIV prevention. Discussion: We examined measures of initiation, coverage and persistence. Among measures of initiation, HIV Prevention–Post Testing would be a useful corollary to Contraceptive Use–Post Partum for a subset of the population. As a measure of coverage, both Net Prevention Coverage and HIV Protection Index (modelled off the Contraception Protection Index) may be useful. Finally, as a measure of persistence, Person‐Years of HIV Protection could be adapted from Couple‐Years Protection. As in contraception, most programs will not reach 100% on HIV prevention metrics but these metrics are highly useful for making comparisons. Conclusions: While we may not be able to perfectly capture the true population of who would benefit from HIV prevention, by building off the work of the contraceptive field to use and refine these metrics, we can assess and compare HIV prevention over time and across programs. Furthermore, these metrics can help us reach global targets, such as the 2025 UNAIDS Goals, and reduce HIV incidence.